Optimalisasi Reformasi Birokrasi dalam Meningkatkan Kinerja Pelayanan Publik: Studi di Desa Buyut Kabupaten Cirebon - Leni Rohida; Iskandar Zulkarnaen (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Bureaucratic reform is an effort to make fundamental changes and renewals to the government administration system. However, bureaucratic reform in recent years has shown that bureaucratic restructuring still requires significant improvements, necessitating a shift in government paradigm. This study aims to identify bureaucratic reforms in optimizing service performance in Buyut Village, Gunung Jati District, Cirebon Regency. This study uses a descriptive empirical method with a qualitative approach. Data sources include secondary and primary data. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out through data reduction, data reading, and drawing conclusions. This study applies public policy theories with the optimization concept proposed by Sirigoringo in 2005, which consists of objectives, decision alternatives, and limiting resources. The results indicate that service performance in Buyut Village, Gunung Jati District, Cirebon Regency is not yet optimal, but there are aspects that still require optimization, particularly the limiting resource indicator. This situation has led some residents of Buyut Village to complain about the lack of adequate facilities, infrastructure, and resources to support the various services provided by the village. Optimizing bureaucratic reform for village government services requires careful attention to these facilities, infrastructure, and resources before implementing this policy.